Switching from blonanserin tablets to blonanserin transdermal patches improves tardive dyskinesia: A case report - Shintaro Sakai; Yoshiro Morimoto; Yusuke Matsuzaka; Takeshi Nakano; Shinji Kanegae; Akira Imamura; Hiroki Ozawa (Wiley, 2021)
Abstract Tardive dyskinesia (TD) is a common side effect of antipsychotics, and it remains a persistent and challenging problem. The blonanserin transdermal patch, developed in Japan and launched in September 2019, is the first antipsychotic transdermal treatment. Here, we describe a patient with schizophrenia who exhibited markedly improved orofacial dyskinesia after switching from blonanserin tablets to blonanserin transdermal patches. We speculate that the patch formulation might have led to more stable plasma blonanserin levels, thus reducing the side effects. Specifically, the patch formulation might have contributed to stable plasma levels via the continuous and direct absorption of blonanserin through the skin.